Anteseden Niat Beli Konsumen pada Produk Janji Jiwa - Razul Riza, Kautsar Isyraaq; Hayuningtias, Kristina Anindita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This article discusses research on three factors that influence consumers' purchase intentions for a coffee shop in Semarang City, these three factors consist of Social Media Marketing, Brand Image and Brand Awareness. Kopi Janji Jiwa is the object chosen in this research which was taken to distribute questionnaires to consumers in the city of Semarang. This research uses primary data obtained from the results of a questionnaire that was filled out by 100 consumers as respondents using the purposive sampling method as an approach. The data processing results from this research used SPSS version 25 software in testing validity tests, reliability tests, model tests and hypothesis tests. Research findings show that Social Media Marketing does not have a significant influence on Purchase Intention to Kopi Janji Jiwa. Brand Image also does not have a significant influence on Intention to Buy Janji Jiwa Coffee, while Brand Awareness has a significant influence on Intention to Buy Janji Jiwa Coffee. From the results of this research it can be concluded that not everyone has the intention to buy just by looking at the Brand Image or Social Media Marketing of a brand, but the majority of respondents have the intention to buy on the basis of brand awareness which can be recognized and remembered in various situations or environments..